2015
DOI: 10.1038/hr.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index and left ventricular mass index with abnormally low and high ankle-brachial indices in chronic kidney disease

Abstract: Obesity, left ventricular hypertrophy (LVH) and peripheral artery disease are frequently noted in patients with chronic kidney disease (CKD), thereby suggesting a close and causal relationship among them. This study was designed to assess whether the combination of an increased body mass index (BMI) and left ventricular mass index (LVMI) are independently associated with abnormally low and high ABI in patients with CKD stages 3-5. A total of 566 patients were included in the study and were classified into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In addition, many factors including pressure overload, renal anemia, malnutrition, and inflammatory status have been reported to be both main causes of the development of LVH and also for atherosclerosis in patients undergoing HD2324. Furthermore, previous studies have demonstrated significantly lower ABI values in patients with LVH than in those without LVH, and that ABI was independently and inversely associated with left ventricular mass index2526. These results suggest that a low ABI may be related to LVH.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, many factors including pressure overload, renal anemia, malnutrition, and inflammatory status have been reported to be both main causes of the development of LVH and also for atherosclerosis in patients undergoing HD2324. Furthermore, previous studies have demonstrated significantly lower ABI values in patients with LVH than in those without LVH, and that ABI was independently and inversely associated with left ventricular mass index2526. These results suggest that a low ABI may be related to LVH.…”
Section: Discussionmentioning
confidence: 77%
“…This result has been confirmed in several subsequent studies 12 . In addition, abnormally low ABI is independently associated with increased LVM in people with hypertension or chronic kidney disease 13,14 . Recently, Hidekazu and co‐workers found that a high ABI in the normal range was significantly associated with ECG‐determined LVH in a cross‐sectional study of Japanese community populations 15 .…”
Section: Introductionmentioning
confidence: 63%
“… 12 In addition, abnormally low ABI is independently associated with increased LVM in people with hypertension or chronic kidney disease. 13 , 14 Recently, Hidekazu and co‐workers found that a high ABI in the normal range was significantly associated with ECG‐determined LVH in a cross‐sectional study of Japanese community populations. 15 However, the relationship between high ABI within the normal range and LVH in patients with hypertension is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PAD was also independently associated with LVMI by a multivariable analysis. It has been shown that, among patients with CKD, those with higher BMI and LVMI tend to have an abnormal ABI [ 26 ]. It has also been suggested that adding ABI to the Framingham risk score may provide a more accurate assessment of all-cause mortality, including cardiovascular death [ 27 ].…”
Section: Discussionmentioning
confidence: 99%